2004
DOI: 10.1097/01.alc.0000141915.56236.40
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Disturbance with Chronicity and Remission of Alcohol Dependence: Data from a Population‐Based Prospective Study

Abstract: Individuals with persistent alcohol dependence have greater odds of insomnia than those whose alcohol dependence remits. The need for prospectively gathered data from community-based samples to assess further the temporal relationships of sleep disturbance, alcohol dependence, and alcohol consumption level is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 49 publications
6
45
2
Order By: Relevance
“…19 Chronic dependence was more commonly associated with insomnia than no history of dependence at 13-year follow-up. 20 A recent study in adolescents found that maternal-rated sleep problems at 3 to 5 years of age (Child Behavior Checklist -Parent Version) in 257 boys from a community-recruited sample of high-risk families predicted early onset of any alcohol use by 12 to 14 years of age. This relationship was not mediated by attention problems, anxiety/depression, or aggression.…”
Section: What Are the Rates Of Co-occurrence Of Insomnia And Alcohol mentioning
confidence: 99%
“…19 Chronic dependence was more commonly associated with insomnia than no history of dependence at 13-year follow-up. 20 A recent study in adolescents found that maternal-rated sleep problems at 3 to 5 years of age (Child Behavior Checklist -Parent Version) in 257 boys from a community-recruited sample of high-risk families predicted early onset of any alcohol use by 12 to 14 years of age. This relationship was not mediated by attention problems, anxiety/depression, or aggression.…”
Section: What Are the Rates Of Co-occurrence Of Insomnia And Alcohol mentioning
confidence: 99%
“…1,2 Individuals with chronic alcohol dependence are 2.6 times as likely to have insomnia as those without such a history. 3 However, the complex relationship between alcohol dependence and insomnia is not well understood, particularly because alcohol dependent patients often have high levels of co-morbid psychiatric and substance use disorders, which confound interpretation. [4][5][6] Many psychiatric disorders such as depression, and symptoms such as suicidal ideation, are also independently associated with insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…, 1997). In patients with alcohol use disorders, insomnia is often part of the withdrawal syndrome and increases risk for relapse (Crum, Ford, Storr, & Chan, 2004;Vitiello, 1997). …”
mentioning
confidence: 99%
“…A recent epidemiological study found that, in the general population, 11% of respondents reported using alcohol specifically to help them sleep (National Sleep Foundation, 2005). Alcohol consumption may initially lead to improved sleep latency, but it is ultimately associated with poorer sleep quality, early wakening, and insomnia (Crum et al, 2004;Foster & Peters, 1999). It remains unclear at this time whether chronic use of alcohol to induce sleep may result in the development of clinically significant abuse or dependence.…”
mentioning
confidence: 99%
See 1 more Smart Citation